2011
DOI: 10.1007/s10646-011-0633-1
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical responses of Lemna minor experimentally exposed to cadmium and zinc

Abstract: The effects of 5 μM cadmium (Cd), a non-essential toxic element and 25 and 50 μM zinc (Zn), an essential micronutrient, were investigated in aquatic plant Lemna minor L. after 4 and 7 days of exposure to each metal alone or to their combinations. Both metals showed tendency to accumulate with time, but when present in combination, they reduced uptake of each other. Cd treatment increased the lipid peroxidation and protein oxidation indicating appearance of oxidative stress. However, Zn supplementation in eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(45 citation statements)
references
References 53 publications
4
41
0
Order By: Relevance
“…Peng et al [50] found that adding Mn to the solution containing Cd significantly improved plant growth and reduced the concentrations of Cd in all organs of the plant. Zn is known to play a crucial role in protein metabolism, gene expression, chromatin structure, and photosynthetic carbon metabolism [51]. In addition, it is associated with the stabilizing and protective effect on biomembranes against oxidative and peroxidative damage, loss of plasma membrane integrity, and alteration of the permeability of the membrane [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Peng et al [50] found that adding Mn to the solution containing Cd significantly improved plant growth and reduced the concentrations of Cd in all organs of the plant. Zn is known to play a crucial role in protein metabolism, gene expression, chromatin structure, and photosynthetic carbon metabolism [51]. In addition, it is associated with the stabilizing and protective effect on biomembranes against oxidative and peroxidative damage, loss of plasma membrane integrity, and alteration of the permeability of the membrane [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…However, proteomic studies of metal stress have been far less numerous and comprehensive in comparison with investigations regarding other environmental stresses in plants (30). Although the processes of heavy metal uptake, accumulation, distribution, oxidative stress induction, and detoxification have been investigated in a wide range of studies on plants (47)(48)(49)(50)(51)(52)(53)(54), the mechanisms involved are still only partially understood. The proteomic approach can therefore help to elucidate new aspects of plant metal stress.…”
Section: The Methodology Of Proteomicsmentioning
confidence: 99%
“…Data sets used for PCA were comprised of 10 variables including growth, Cd, Zn, and Cu accumulation, Chl a,Chl b, total chlorophylls and carotenoid content, maximum quantum yield (F v /F m ) and effective quantum yield (∆F/F' m ). Also, malondialdehyde (MDA) content, reported previously (31,32), was added as a variable representing oxidative stress parameter. PCA was applied to the standardised data set and the factor loadings were classified as "strong", "moderate", and "weak" corresponding to absolute loading values of >0.75, 0.75-0.50, and 0.50-0.30, respectively (42).…”
Section: Discussionmentioning
confidence: 99%
“…Cd inhibits Chl biosynthesis through δ-aminolevulinic acid dehydratase and protochlorophyllide reductase due to interaction with -SH groups which leads to a diminished production of δ-aminolevulinic acid -the first common precursor for all tetrapyrroles (29). The observed effect of CdCl 2 on pigments could partly be caused by Cd-induced oxidative stress (31). Contrary to redox active metals, Cd is involved in the production of ROS indirectly -by interactions with antioxidative defence system, substitution of essential elements at enzyme active sites, and disruption of electron transport chain (29,50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation